39th Winter School on Vibroacoustical Hazards Suppressions Szczyrk, Poland, February 28 – March 4, 2011 - BUKOWSKI, Roman (Archives of Acoustics, 2011)
Traditionally I invite you to acquaint with the preliminary list of lectures and some abstracts of lectures submitted for presentation in the 39th Winter School on Vibroacoustical Hazards Suppressions. This national School, organized by Upper Silesian Division of the Polish Acoustical Society and Institute of Physics at the Silesian University of Technology, is planned this year at the turn of February and March 2011. This conference is organized in different places of Silesian Beskidy Mountains, but this year will be again organized in Szczyrk. The conference is the forum for all environmental vibroacoustics fields. Particularly it concerns the traffic noise, industry noise, vibroacoustics of machines, room acoustics, noise protection and similar problems. During the School, the theoretical works, experimental, measuring, technical, applied and normative ones are presented. The School lectures, and other conference materials, will be published in the “Materials of the XXXVIX Winter School on Vibroacoustical Hazards Suppressions” (in Polish) edited by dr. Roman Bukowski and dr. Mieczysław Roczniak (chairman of the conference). This publication is intended for participants of the School and for many libraries in Poland.